Investigation of genetic mechanism of the Shigang fault zone in the Northern Jiangsu Basin using physical analog sand-box modeling. (November 2022) - Li, Xiyuan
Abstract: The Shigang fault zone in Jinhu Sag plays a significant role in the evolution of sag and hydrocarbon accumulation. This paper studies the tectonic evolution history of the critical profiles of the Shigang fault zone by dissecting these profiles. According to the 3D seismic interpretations and the characteristics of the geological structure of the Northern Jiangsu Basin, this paper proposes that the Shigang fault zone was formed by the tectonic evolution of the basement faults reactivation before the basin formed in the late Cretaceous-Paleogene. In addition, the Shigang fault is the same foreland thrust fault in the southern margin of the Sulu Orogenic Belt in the Indosinian period. During the late Cretaceous-Paleogene basin-forming period, the Shigang fault was reactivation and changed from a thrust fault to a basin-controlled listric fault. Under the oblique extension condition, the Shigang fault was resurrected, and the right-lateral strike-slip controlled the shallow cap, forming a negative flower structure. It controls the shallow faults in the Shigang fault zone to form en echelon fault system. The shallow faults controlling the Shigang fault zone constitute an echelon fault system. The sedimentary filling formation, the physical properties of the formation, and the dip angle of the pre-existing basement faults are analyzed to validate the rationality of the conclusion on the geological formation of the Shigang fault zone. Physical analog sand-box experiments with multiple models are designed and performed to reveal the formation of the Shigang fault zone. The analysis of the simulation results indicates that the experiment of the normal basement fault with 10 mm thickness silica gel and a dip angle of 75° (soft layer in the Fu-4 Member) has a high degree of similarity with the geological understanding. The experimental results illustrate the characteristics of the dynamic formation mechanism and tectonic evolution in the Shigang fault zone and verify the genetic mechanism of the Shigang fault and the reliability of the conclusions and cognitions obtained from the analysis of the structural control of the overlying sedimentary layers. Furthermore, the physical analog sand-box modeling has a broad application prospect in investigating the structural formation mechanism.